PEMANFAATAN PANEL SURYA ON GRID PADA RUMAH TINGGAL BERDASARKAN JUMLAH BEBAN - Patabang, Simon (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Savings in electricity consumption at this time is something to note because the growth of electricity load in urban areas is very fast while the growth of power plants tends to be slow. One way to save PLN electricity consumption is to utilize solar panels as an alternative energy source, where some or all of the electricity load can be transferred to solar power plants (PLTS) on the grid. The research was conducted by load design methods and simulations of the loading of electrical power. The power generated by PLTS on grid is calculated based on the level of solar radiation, ranging from 06:30 to 18:00. Based on the results of the analysis obtained that by using PLTS on grid as an alternative energy source in residential homes, it can provide savings in PLN electricity consumption of 34.78% to 89.54%. These results show that the use of PLTS on grid is very suitable for its use in urban areas in order to support electricity saving policies